2018
DOI: 10.1590/0037-8682-0112-2017
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological factors associated with Toxoplasma gondii infection in postpartum women treated in the public healthcare system of Goiânia, State of Goiás, Brazil

Abstract: Our findings concur with the results of other studies conducted in Brazil and abroad, where variables such as low levels of schooling, and advanced age (≥ 30 years) are major risk factors for pregnant women to become infected with T. gondii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
3
12
0
7
Order By: Relevance
“…The prevalence of T. gondii infection increases with age and the bivariate logistic regression analysis showed that there was a statistical association between the age groups and the positivity for IgG anti-T. gondii, with a higher probability of prior exposure for those aged 25 and over. These results were similar to the findings of most surveys that included not only pregnant women, postpartum and of reproductive age, but also those in the general population [32,33] and could be explained by the increase in exposure to sources of infection throughout life [34,35].…”
Section: Plos Onesupporting
confidence: 88%
“…The prevalence of T. gondii infection increases with age and the bivariate logistic regression analysis showed that there was a statistical association between the age groups and the positivity for IgG anti-T. gondii, with a higher probability of prior exposure for those aged 25 and over. These results were similar to the findings of most surveys that included not only pregnant women, postpartum and of reproductive age, but also those in the general population [32,33] and could be explained by the increase in exposure to sources of infection throughout life [34,35].…”
Section: Plos Onesupporting
confidence: 88%
“…This suggests that factors affecting the risk of infection are more complex than a simple urban-rural division and may be confounded by other factors. This association was also found in other studies from Iran and Brazil 6,[11][12][13] .…”
Section: /6supporting
confidence: 88%
“…Through multivariate analysis, we found that the presence of cats had no association with the seroprevalence of toxoplasmosis in pregnancy. No association was also observed in other studies investigating the association between seroprevalence and the presence of household cats in Brazil 10,13 . However, some studies from Burkina Faso and Iran have shown an association 6,12 .…”
Section: /6mentioning
confidence: 56%
See 2 more Smart Citations